La tecnologia di rilevamento a fibre ottiche - Redazione MediaGEO (GEOmedia)
Fiber optic sensing utilizes optical fibers to detect and monitor real-time vibrations and temperature changes in the ground. This type of sensing is capable of identifying a wide range of phenomena, including vehicles driving or stopping, people walking, running, climbing, or digging, seismic activity, and changes in structural integrity, such as an explosion.